The household knights of King John - Church, S. D. (Cambridge University Press, 1999)
This is the first full-length study of the elite group which surrounded King John, the household knights. As well as fighting for the king, they organised his armies, were involved in government, undertook diplomatic missions, controlled important castles, and proved themselves generally indispensable for the workings of English medieval government.
Keywords: Great Britain -- History -- John, 1199-1216.; Knights and knighthood -- Great Britain -- History -- To 1500.; Royal households -- Great Britain -- History -- To 1500.; Great Britain -- History, Military -- 1066-1485.; Grande-Bretagne -- Histoire -- 1199-1216 (Jean); Grande-Bretagne -- Histoire militaire -- 1066-1485.; HISTORY.; Knights and knighthood; Royal households; Great Britain; Hofhouding.; Ridders.; Engeland.; To 1500; History; Military history